The debate over open access is missing the point. Issue 2 (3rd January 2019) - Buck, Stuart
Abstract : Key points It is more important to a funder to know that the research advances knowledge and has an impact on the field than that it is published in a prestigious journal (or not). Improving journal quality assurance is more important than improving the business model. Focusing on open access misses the point that journals need to improve their quality standards.